Exploring the economics of public health intervention scale-up: a case study of the Supporting Healthy Image, Nutrition and Exercise (SHINE) cluster randomised controlled trial - Vicki Brown; Huong Tran; Joanne Williams; Rachel Laws; Marj Moodie (BMC, 2022)
Abstract Background The costs and benefits of an intervention within the intervention testing phase may differ from those experienced when that intervention is implemented and delivered at scale. Yet limited empirical work has been undertaken to explore how economic constructs related to implementation and scale-up might have an impact on intervention cost. The aim of this study was to explore the potential economic impacts of implementation and scale-up on a healthy weight and body image intervention tested in a Type II translational research trial. Methods The Supporting Healthy Image, Nutrition and Exercise (SHINE) study is a cluster randomised controlled trial, aiming to deliver universal education about healthy nutrition, physical activity and wellbeing behaviours to adolescents in Australian secondary schools. Data on the cost of the intervention were collected alongside the trial using standard micro-costing techniques. Semi-structured interviews were conducted with key intervention stakeholders to explore the potential economic impacts of implementation and scale-up. Thematic content analysis was undertaken by two authors. Results Fifteen intervention group schools participated in the 8-week online intervention targeting students in 2019 (99 Grade 7 classes; 2,240 students). Booster sessions were delivered during one class session in Grades 8 and 9, in 2020 and 2021 respectively. Time costs of intervention delivery and co-ordination comprised the majority (90%) of intervention cost as per the trial, along with costs associated with travel for intervention training and equipment. Themes related to the benefit of the intervention emerged from interviews with six intervention stakeholders, including the potential for economies of scale afforded by online delivery. Contextual themes that may have an impact on intervention implementation and scale included acceptability across all school sectors, availability and reliability of IT infrastructure for intervention delivery and variations in population characteristics. A number of key alterations to the intervention program emerged as important in supporting and sustaining intervention scale-up. In addition, significant implementation costs were identified if the intervention was to be successfully implemented at scale. Conclusions The findings from this study provide important information relevant to decisions on progression to a Type III implementation trial, including budget allocation, and will inform modelled economic evaluation.